2011
DOI: 10.1108/00012531111165003
|View full text |Cite
|
Sign up to set email alerts
|

The use and value of local information systems

Abstract: Purpose -This paper aims to show that there has been a rise in the development of local information systems in recent years. However, little research exists on users' perspectives of the value they obtain from these systems. This paper seeks to directly address this issue. Design/methodology/approach -A case study approach was employed. The system selected for the case study was the Milton Keynes intelligence (MKi) Observatory, which is managed by Milton Keynes Council. Interviews with key staff involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…One suggestion derived from these findings is that FAs should both raise awareness and work to improve ICT skills to optimize their internal structure or context in order to succeed in their digitalization. The use of this approach can further aid FAs in their realization of the full potential of ICT, as also evidenced by Oakford and Williams (2011), who showed that users will use technology once they are aware of and understand the benefits and approaches.…”
Section: Discussionmentioning
confidence: 89%
“…One suggestion derived from these findings is that FAs should both raise awareness and work to improve ICT skills to optimize their internal structure or context in order to succeed in their digitalization. The use of this approach can further aid FAs in their realization of the full potential of ICT, as also evidenced by Oakford and Williams (2011), who showed that users will use technology once they are aware of and understand the benefits and approaches.…”
Section: Discussionmentioning
confidence: 89%